Comparison of the Oncological Outcomes Between Robot-Assisted and Abdominal Radical Hysterectomy for Cervical Cancer Based on the New FIGO 2018 Staging System: A Multicentre Retrospective Study - Li, Pengfei; Zhan, Xuemei; Lv, Chifei; Lin, Zhong; Yang, Ying; Wang, Wuliang; Wang, Shaoguang; Hao, Min; Zhu, Bin; Bin, Xiaonong; Lang, Jinghe; Liu, Ping; et al. (Frontiers in Oncology, 2022)
Objective To compare the 3-year oncological outcomes of robot-assisted radical hysterectomy (RRH) and abdominal radical hysterectomy (ARH) for cervical cancer. Methods Based on the clinical diagnosis and treatment for cervical cancer in the China database, patients with FIGO 2018 stage IA with lymphovascular space invasion (LVSI)-IB2 cervical cancer disease who underwent RRH and ARH from 2004 to 2018 were included. Kaplan–Meier survival analysis was used to compare the 3-year overall survival (OS) and disease-free survival (DFS) rate between patients receiving RRH and those receiving ARH. The Cox proportional hazards model and propensity score matching were used to estimate the surgical approach-specific survival. Results A total of 1,137 patients with cervical cancer were enrolled in this study, including the RRH group (n = 468) and the ARH group (n = 669). The median follow-up time was 45 months (RRH group vs. ARH group: 24 vs. 60 months). Among the overall study population, there was no significant difference in 3-year OS and DFS between the RRH group and the ARH group (OS: 95.8% vs. 97.6% p = 0.244). The Cox proportional hazards analysis showed that RRH was not an independent risk factor for 3-year OS (HR: 1.394, 95% CI: 0.552–3.523, p = 0.482). However, RRH was an independent risk factor for 3-year DFS (HR: 1.985, 95% CI: 1.078–3.655 p = 0.028). After 1:1 propensity score matching, there was no significant difference in 3-year OS between the RRH group and the ARH group (96.6% vs. 98.0%, p = 0.470); however, the 3-year DFS of the RRH group was lower than that of the ARH group (91.0% vs. 96.1%, p = 0.025). The Cox proportional hazards analysis revealed that RRH was not an independent risk factor for 3-year OS (HR: 1.622, 95% CI: 0.449–5.860 p = 0.461), but RRH was an independent risk factor for 3-year DFS (HR: 2.498, 95% CI: 1.123–5.557 p = 0.025). Conclusion Among patients with stage I A1 (LVSI +)-I B2 cervical cancer based on the FIGO 2018 staging system, RRH has a lower 3-year DFS than ARH, suggesting that RRH may not be suitable for early cervical cancer patients.